Wound Healing Potential of the Standardized Extract of Boswellia serrata on Experimental Diabetic Foot Ulcer via Inhibition of Inflammatory, Angiogenetic and Apoptotic Markers - Pengzong, Zhang; Yuanmin, Li; Xiaoming, Xiong; Shang, Deng; Wei, Xiong; Zhigang, Lang; Dongzhou, Du; Wenjing, Yu; Jianbiao, Yue; Yang, Xiang; Xia, Li (Planta Medica, 2019)
The aim of the present study was to evaluate the wound healing potential and possible mechanism of action of the standardized extract of Boswellia serrata against the experimental model of diabetic foot ulcer. α-Boswellic acid was isolated from the standardized extract of B. serrata and characterized (HPLC, 1H-NMR, 13C-NMR, ESI-MS). Diabetes was induced in Sprague-Dawley rats by streptozotocin (55 mg/kg, i. p.), and wounds were created on the dorsal surface of the hind paw. B. serrata (100, 200, and 400 mg/kg, p. o.) was administered to the rats for 16 days. The HPLC analysis showed a single peak with a retention time of 12.51 min. The compound was identified with ESI-MS [M + Na]+ = 455.37 as α-boswellic acid. Treatment with B. serrata (200 and 400 mg/kg) significantly increased the rate of wound contraction via modulation of oxido-nitrosative stress and elevated the hydroxyproline level at the wound area. reverse transcription-PCR analysis revealed that streptozotocin-induced increases in TNF-α, interleukin-1β, interleukin-6, nuclear factor-kappa-light-chain-enhancer of activated B cells, and Bcl-2-associated X protein, and decreases in angiopoietin-1, Tie2, transforming growth factor beta 1, vascular endothelial growth factor, and collagen-1 mRNA expression were significantly inhibited by B. serrata. It also significantly reduced wound cellular necrosis as evaluated by flow cytometry using propidium iodide fluorescence intensity. Streptozotocin-induced histopathological alterations were also significantly ameliorated by B. serrata. In conclusion, standardized extracts of B. serrata exert its wound healing potential via orchestrating mechanisms, which include the inhibition of oxido-inflammatory markers (oxido-nitrosative stress, TNF-α, interleukins, and nuclear factor-kappa-light-chain-enhancer of activated B cells), increased collagen synthesis (hydroxyproline and collagen-1) and angiogenesis (Ang-1/Tie2), promoting growth factors (transforming growth factor beta 1 and vascular endothelial growth factor), and inhibition of apoptosis (Bcl-2-associated X protein) to accelerate wound healing in experimental delayed diabetic foot ulcer.
Keywords: Ang-1/Tie2; Boswellia serrata; Burseraceae; collagen-1; diabetic foot ulcer; TGF-β; α-boswellic acid